Geophysical and Hydrologic Studies of Lake Seepage Variability. Issue 6 (31st December 2014) - Toran, Laura; Nyquist, Jonathan; Rosenberry, Donald; Gagliano, Michael; Mitchell, Natasha; Mikochik, James
Abstract: Variations in lake seepage were studied along a 130 m shoreline of Mirror Lake NH. Seepage was downward from the lake to groundwater; rates measured from 28 seepage meters varied from 0 to −282 cm/d. Causes of this variation were investigated using electrical resistivity surveys and lakebed sediment characterization. Two‐dimensional (2D) resistivity surveys showed a transition in lakebed sediments from outwash to till that correlated with high‐ and low‐seepage zones, respectively. However, the 2D survey was not able to predict smaller scale variations within these facies. In the outwash, fast seepage was associated with permeability variations in a thin (2 cm) layer of sediments at the top of the lakebed. In the till, where seepage was slower than that in the outwash, a three‐dimensional resistivity survey mapped a point of high seepage associated with heterogeneity (lower resistivity and likely higher permeability). Points of focused flow across the sediment–water interface are difficult to detect and can transmit a large percentage of total exchange. Using a series of electrical resistivity geophysical methods in combination with hydrologic data to locate heterogeneities that affect seepage rates can help guide seepage meter placement. Improving our understanding of the causes and types of heterogeneity in lake seepage will provide better data for lake budgets and prediction of mass transfer of solutes or contaminants between lakes and groundwater.